2015
DOI: 10.2500/ajra.2015.29.4204
|View full text |Cite
|
Sign up to set email alerts
|

Is Sex an Independent Prognostic Factor in Esthesioneuroblastoma?

Abstract: Male patients with ENB seemed to have significantly worse DSS at 10 years than female patients. This disparity seems to be due to higher grade and stage in male patients at presentation. After accounting for these two factors, the prognosis of male patients was not found to be significantly different from that of female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…CRC is one of the most common cancers all over the world (1). There are many differences between males and females in morbidity, mortality, prognosis, and biological behaviour for most cancers (19)(20)(21)(22)(23)(24). The sex differences in cancer survival have attracted great attention because they may be a signal of basic biological differences between males and females in cancer pathogenesis and treatment response, which can be incorporated into management strategies (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…CRC is one of the most common cancers all over the world (1). There are many differences between males and females in morbidity, mortality, prognosis, and biological behaviour for most cancers (19)(20)(21)(22)(23)(24). The sex differences in cancer survival have attracted great attention because they may be a signal of basic biological differences between males and females in cancer pathogenesis and treatment response, which can be incorporated into management strategies (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram is a new form of disease risk estimation that can aid clinical decision making (Botticelli et al, 2019). Studies based on the Surveillance, Epidemiology, and End Results Program (SEER) database showed that gender had no significant difference in the OS of neuroblastoma in children (Stokes et al, 2015). These results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying patients at risk of poor outcome can potentially help to guide the need for adjuvant treatment. These studies have found improved survival with age less than 60 years, female sex, having private health insurance, lower tumor grade, lower Kadish stage, N0 neck status, and margin‐negative resection . Furthermore, male patients were found to present with higher‐grade disease and a trend toward higher stage .…”
Section: Sinonasal Malignanciesmentioning
confidence: 96%